Enrolling into a humaniversity and understanding the meaning of education - Paramboor, Jafar (2020)
During an interview session, one of the questions posed to me by the panelist was something related to the current scenario of university education. Specifically, the question came in the form of this statement: ‘It has been said that universities should not be degree mills but centres of knowledge dissemination and creativity.' Give us your take on that. Here I have expanded the ideas on which my response went on as follows: